Thickness of Lower Trapezius Muscle in Women with Chronic Unilateral Neck Pain - Kanokon Kawsoiy (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Lower trapzius muscle has an important role in scapular stabilization. Many studies have demonstrated the contribution of lower trapezius muscle to pain in the cervical spine. The aims of the study were to examine thickness of the lower trapezius muscle using ultrasound imaging in patients with chronic unilateral neck pain and to determine relationships of the lower trapezius muscle thickness and pain intensity and disability. Twenty women with chronic unilateral neck pain (mean age 25.65 ± 3.69 years) and 20 controls (mean age 25.80 ± 4.55 years) participated in the study. The lower trapezius muscle thickness was measured bilaterally twice at rest at T8 spinous process using ultrasound imaging. Measurements of each image were made using Image J software program. The results demonstrated smaller thickness of the lower trapezius muscle in the side ipsilateral to pain in patients with neck pain compared to controls (p < 0.05). There was no significant difference in the thickness of the lower trapezius muscle between the ipsilateral and contralateral sides (p > 0.05). In the control group, the lower trapezius muscle thickness on the right (dominant) side was greater than that in the left (non-dominant) side (p < 0.05). The lower trapezius muscle thickness was not correlated with pain intensity and neck disability (p > 0.05). The study suggests that patients with unilateral neck pain have decreased thickness of the lower trapezius muscle ipsilateral to pain. Influence of side of pain and hand dominance must be considered when investigating size of the lower trapezius muscle.